Smartphone Addiction among Medical Interns: Results and Implications from a Cross-sectional Observational Study - Bhumika Tekchandani, Sonali Sharma, Smriti Kayat (RUHS Journal of Health Sciences)
Introduction: Smartphone addiction (SA) has become a growing concern, particularly among medical interns in high-stress environments. This cross-sectional study investigated smartphone addiction prevalence and its association with accidental injuries among medical interns at an Indian university medical college. Methodology: 85 medical interns (39 % female; 61 % male), average age 24.31 years, were enrolled. The Smartphone Addiction Scale-Short Version (SAS-SV) assessed smartphone addiction, and self-disclosure questionnaires collected data on accidental injuries and smartphone usage patterns. Results: 62.35 % of participants were classified as smartphone addicts, with a significant association between gender and addiction (p 0.036). Urban residents had more addiction than rural residents (p < 0.05). Longer smartphone use duration was strongly linked to addiction (p < 0.001). Addicted individuals reported more phone time (6.17 hours) than non-addicts (4.84 hours) and engaged more in talking, web surfing, entertainment, and social networking (p < 0.05). Participants reporting no accidents while using phones had lower odds of addiction (OR 0.018, 95% CI: 0.000-0.745, p 0.034). Bumps, collisions, or tripping were more frequent among addicts (89%) than non-addicts (11%) (p < 0.001). Conclusion: The findings highlight high SA prevalence among medical interns and its association with accidental injuries, emphasizing the need for preventive measures and further research to mitigate risks and promote healthier technology use among medical professionals in training.